Comparative anatomical outcomes of high-flow vs. low-flow phacoemulsification cataract surgery: A systematic review and meta-analysis - Kuo, Po-Chin; Hung, Jia-Horung; Su, Yu-Chen; Fang, Ching-Ju; Lee, Chaw-Ning; Huang, Yi-Hsun; Shao, Shih-Chieh; Lai, Edward Chia-Cheng (Frontiers in Medicine, 2022)
Background Phacoemulsification is an effective and widely performed technique in cataract surgery, but the comparative anatomical outcomes, including endothelial cell loss (ECL), central corneal thickness (CCT), and central macular thickness (CMT), between high-flow and low-flow phacoemulsification cataract surgery remain unclear. Methods This study followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. Random-effects models were applied to measure pooled mean differences (MD) with 95% confidence intervals (CI) of anatomical outcomes between high-flow and low-flow phacoemulsification cataract surgery. We judged overall certainty of evidence (CoE) based on Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Results We included six randomized controlled trials (RCTs) totaling 477 participants. The meta-analysis showed similar changes associated with these two surgery types in both ECL at postoperative days 2–14 (MD: −1.63%; 95% CI: −3.73 to 0.47%; CoE: very low), days 15–42 (MD: −0.65%; 95% CI −2.96 to 1.65%; CoE: very low) and day 43 to month 18 (MD: −0.35%; 95% CI: −1.48 to 0.78%; CoE: very low), and CCT at postoperative day 1 (MD: −16.37 μm; 95% CI: −56.91 to 24.17 μm; CoE: very low), days 2–14 (MD: −10.92 μm; 95% CI: −30.00 to 8.16 μm; CoE: very low) and days 15–42 (MD: −2.76 μm; 95% CI: −5.75 to 0.24 μm; CoE: low). By contrast, low-flow phacoemulsification showed less increase in CMT at postoperative days 15–42 (MD, −4.58 μm; 95% CI: −6.3 to −2.86 μm; CoE: low). Conclusions We found similar anatomical outcomes, except in CMT, for both high-flow and low-flow phacoemulsification cataract surgery. Future head-to-head RCTs on visual outcomes should confirm our findings. Systematic review registration PROSPERO, identifier: CRD42022297036.